"Meddling with Sorcery": Hypnotism, the Occult and the Return of Forsaken Women in the 1890s Ghost Stories of Lettice Galbraith. Issue 2 (3rd April 2022) - Liggins, Emma
Abstract: Lettice Galbraith's ghost stories are largely excluded from histories of the Victorian supernatural. Despite writing within a genre popular in the 1890s, little is known of her biography, her literary circle or her influences. Like other 1890s writers, Galbraith capitalised on public fascination with the tropes of crime narratives – the foggy London streets, the sensational newspaper snippets, violence and suppressed scandal – as well as the fascination with hypnotism and the occult revival. In the stories "In the Séance Room" and "The Missing Model" (1893) the wronged woman, abandoned, mistreated and objectified, returns as a terrifying spirit, who manifests in disturbing form to shame professional men. The séance room and the art gallery admit the excluded woman who silently petitions for her lost story to be told: the ghostly women have "magnetic" stares, subverting power relations in contemporary discourses of hypnotism. In "The Blue Room" (1897) women's attempts to summon a demon have dangerous consequences and are seen as "meddling with sorcery". Borrowing from the crime narrative with its mysteries, clues, detection and fake identities, Galbraith refashions the Victorian ghost story to hold men accountable for their deception and violence and addresses fears about black magic and hypnotism.